Islamic Entrepreurial Values Intention Determinants: An Empirical Model And Case Of Micro Entrepreneurs In Solo Raya Regency - Arif Julianto Sri Nugroho; Anis Marjukah; Abdul Harris; Anna Febrianty; Tasari Tasari (Benefit: Jurnal Manajemen dan Bisnis, 2021)
Independent enterprises that are able to exist and survive for several generations and are able to achieve the dreams they aspire to are the hopes of every founder. There are many factors that determine the success of an entrepreneur to survive the tough competition. These factors include the ability to respond internal and external changes quickly and accurately. The ability to win the competition, be able to know the situation, collaborate with other parties to work together and the ability to adapt to competition are the keys to business sustainability. The massive Covid-19 condition is a challenge for independent Moslem micro entrepreneurs to survive.This research aims to test the model whether the attitude values in the form of the concept of Islamic entrepreneurs, social responsibility, local cultural wisdom values have a significant influence on entrepreneurial intentions and entrepreneurial behavior. The research design is carried out using quantitative methods which explain the causal relationship of one dependent variable which is influenced by several independent variables to be tested. Hypothesis testing is formulated using a multivariate analysis model uses SEM ( Structural Equation Model). The population in the research is Moslem micro-entrepreneurs in Solo Raya Regency. The research sampling technique is conducted through purposive sampling of 165 respondents.The analysis results show that all research hypotheses are supported. Antecedents of entrepreneurial intentions in the form of Islamic entrepreneurial values, Islamic social responsibility and local cultural wisdom have a positive influence and influence on behavior